[AIDS and the future of Africa] - (:unkn) unknown (My University, 1994)
[First examine the tools to make the size of the AIDS pandemic. AIDS appears as an urban disease that diffuses into the countryside. Typed geographically HIV affects people differently according to age and gender. Just as AIDS in Africa has a distinct mode of transmission of the North (dominated by cases among gay men and drug addicts who take drugs intravenously), it causes on the continent to be specified. The apprehension of the AIDS epidemic in Africa allows it to predict the future? Should be used for this demographic perspectives methods including analyzing the factors that allow the choice of assumptions.]
Keywords: African Research